2001
DOI: 10.1071/ah010051
|View full text |Cite
|
Sign up to set email alerts
|

Cost-analysis of gym-based versus home-based cardiac rehabilitation programs

Abstract: A cost-analysis of an existing gym-based program was compared with a proposed home-based program for delivering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Failure to include such costs hides a shifting of costs to patients. In addition, the majority of previous economic analyses had a more intensive centre-based programme than are standard in the UK 28,29,31,95,97,98 and had less home visiting than was provided in this study. 100 Although the cost per patient in the centre-based arm in BRUM was lower than in the HTA survey 63 (£157 in BRUM versus £220 per patient referred), much of this difference is due to the BRUM centrebased costs including a narrower range of services and focusing on Phase III of the CR programme whereas the HTA survey included the whole CR service costs divided between the number of CR participants.…”
Section: Economic Study Findingsmentioning
confidence: 94%
See 1 more Smart Citation
“…Failure to include such costs hides a shifting of costs to patients. In addition, the majority of previous economic analyses had a more intensive centre-based programme than are standard in the UK 28,29,31,95,97,98 and had less home visiting than was provided in this study. 100 Although the cost per patient in the centre-based arm in BRUM was lower than in the HTA survey 63 (£157 in BRUM versus £220 per patient referred), much of this difference is due to the BRUM centrebased costs including a narrower range of services and focusing on Phase III of the CR programme whereas the HTA survey included the whole CR service costs divided between the number of CR participants.…”
Section: Economic Study Findingsmentioning
confidence: 94%
“…95 One systematic review of economic evaluations of CR which compared home-based with supervised CR has been published. 96 This identified four evaluations of home-based CR compared with supervised provision 28,97,98 and one study has been published after the review. 99 Of the five evaluations, four were in the context of RCTs with follow-up from 6 months to 2 years.…”
Section: Economic and Costing Studiesmentioning
confidence: 99%
“…This is already clearly acknowledged in cardiac rehabilitation, stroke and brain injury in terms of avoiding costly readmissions to hospital at a later date [36,37]. Health service expenditure was an important driver of overall cost estimates in this study.…”
Section: Discussionmentioning
confidence: 92%
“…9 To address these barriers and the vast underutilization, a number of alternative delivery methods have been investigated including CR programs distributed over 12 months, intermittent home visits, web-based interventions, and telephone-based programs with varying success. [10][11][12][13][14][15] The Veterans Health Administration (VA) is a large integrated health care system with approximately 8000 admissions for acute MI, and nearly 14000 PCI and 5000 CABG procedures annually. Investigation of CR utilization within the VA revealed that only 28% (35 of the 124) facilities have a CR program.…”
mentioning
confidence: 99%